Analisis Nilai Pendidikan Karakter dalam Novel Kado Terbaik Karya JS Khairen - Santa Rosa Br Pardosi; Achmad Yuhdi (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
Abstract The purpose of this study is to describe the values of character education in the novel Kado Terbaik by J.S Khairen.Â This research uses descriptive qualitative method with content analysis method. The data source of this research is the novel Kado Terbaik by J.S Khairen. The data collection technique is reading and writing technique. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Based on the results of the study, there are character values contained in the novel Kado Terbaik by J. S Khairen, including 6 excerpts. S Khairen, among others, 6 snippets of religious values that illustrate the character's adherence to religious teachings, 4 snippets of honest values that illustrate the character's honesty through words and actions, 1 snippet of tolerance values reflected in the attitude of the characters who show mutual respect despite differences in social status, 3 snippets of hard work values described through Rizki's character who tries to fulfill his own needs, 1 snippet of independent values reflected through Rizki's character who lives alone without depending on others. 4 snippets of curiosity values, 4 snippets of curiosity value reflected in the conversation between the characters, 1 excerpt of the value of respect for achievement reflected in the actions of Bang Toron's character, 3 snippets of friendly/communicative value reflected in the relationship between Rizka, Singlet, and Gembil, 2 snippets of peace-loving value reflected in the actions of Rani's father, 6 snippets of social care value reflected in the actions of the characters, and 2 snippets of responsibility value shown by Rizki's character. Keywords: Education, character, novel, J.S Khairen